Meningkatkan Kopetensi Guru Bahasa Indonesia Melalui Program Pengembangan Profesional - Grisma Yuli Arta; Wendrizal Wendrizal; Aulia Almeyda (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study examines the effectiveness of professional development programs for Indonesian language teachers at SMA 2 and SMA 9 Sijunjung in improving their teaching competence. The focus of the research includes analysis of improving teaching competence, student involvement, and creativity in teaching after participating in the program. The research method used included observation and interviews with the five teachers involved. The results of the study show that professional development programs have a significant positive impact. Teachers have experienced an increase in the application of innovative teaching methodologies and the use of educational technology. Student involvement in the learning process also increases, characterized by active participation in class discussions and assignments. The use of digital media such as learning videos and podcasts helps increase teachers' creativity in delivering more interesting and relevant material. In conclusion, professional development programs play an important role in supporting the improvement of the quality of Indonesian education, with positive implications for developing students' potential and preparing them for an increasingly complex future..